Pemberian Aktivitas Fisik Terhadap Memori Jangka Pendek Anak Usia 8-10 Tahun - Rahma Aghnia Tazkiriani; Ramadoni .; Ryan Febriyanto Al Hasan; Rossa Anggita Lisdianti; Sulistyanti Winda Yanznur; Ganesa Puput Dinda Kurniawan; Ari Sudarsono (Jurnal Pengabdian Masyarakat Fisioterapi dan Kesehatan Indonesia, 2022)
Background: Cognitive is the ability to recognize and interpret a person to environment, such as memory. The speed of cognitive processing is influenced by the degree of activation of short-term memory which play a role in helping humans in the learning process. Physical activity can be one method to improve short-term memory because it can improve attention and cognitive performance for example, problem solving and memory. A positive correlation was found between physical activity and better working memory among children aged 8-10 years. Purpose: This community service aims to introduce physiotherapy to the community and increase knowledge and awareness regarding the importance of physical activity to improve cognitive function, especially in children aged 8-10 years. Method: This activity is a pre-experimental design with one group pre-post test design without a control group using a quota sampling technique. Result: . There is a significant increase, namely 49% in the short-term memory of children aged 8-10 years after doing physical activity with aerobic methods and agility exercise as measured by the digit span test. Conclusion: Physical activity with aerobic methods and agility exercise is effective to improve short-term memory function in children aged 8-10 years.